THE IMPACT OF SOCIAL MEDIA ON TEENAGERS - Tupliyeva Ruxshona; Eldorbek Khamitov (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article explores the multifaceted impact of social media on teenagers, focusing on both its positive and negative effects. The study examines how platforms such as Instagram, TikTok, Snapchat, and others influence adolescents’ psychological well-being, self-esteem, academic performance, and social interactions. It highlights the increasing role of virtual communication in shaping teenagers’ identities, peer relationships, and time management. Special attention is given to the correlation between excessive social media usage and issues such as anxiety, depression, cyberbullying, and sleep disturbances. At the same time, the article acknowledges the potential benefits of social media, including increased access to information, opportunities for self-expression, and the development of digital skills. Supported by recent scientific research, statistical data, and expert opinions, the article aims to provide a balanced perspective. It also includes practical recommendations for parents, educators, and mental health professionals on how to guide teenagers toward safer and more productive use of social media.